KARAKTERISTIK KONSUMSI MASYARAKAT BERDASARKAN JENIS PEKERJAAN DI PANGKALAN KERINCI - rahmi zulkhiati; Rery Novio (JURNAL BUANA, 2023)
Rahmi. COMMUNITY CONSUMPTION CHARACTERISTICS BY TYPE OF WORK IN PANGKALAN KERINCI Thesis, Padang: Faculty of Social Sciences, Padang State University 2022. This study aims to (1) describe the characteristics of family consumption in the district. Pangkalan Kerinci, Kab. Pelalawan. (2) describe the pattern of settlement between ASN and private employees in Kec. Pangkalan Kerinci, Kab. Pelalawan.This type of research is descriptive quantitative. Data collection techniques using observation, documentation and questionnaires. And the data analysis technique uses data percentage and nearest neighbor analysis The results of this study (1) Consumption Characteristics People's income based on occupation Private employees and State Civil Apparatus have a salary of 3-5 million per month. Private employees and State Civil Apparatus have additional and sufficient income in living their daily lives. In terms of income and financial expenses Private employees are sufficient due to the facilities provided by the company, while the average State Civil Apparatus ownership of assets is private voting (2) Based on the main functions of the living environment and the environment that supports livelihoods pattern of distribution of community settlements between State Civil Apparatus and private employees has a ratio of 0.600743 and a ratio of 0.589348 which means it has a clustered pattern. KEYWORD: Nearest Neighbor Analysis, Consumption Characteristics, Distribution patter